MGluR1/5 activation in the lateral hypothalamus increases food intake via the endocannabinoid system. (19th September 2016) - Sánchez-Fuentes, Asai; Marichal-Cancino, Bruno A.; Méndez-Díaz, Mónica; Becerril-Meléndez, Alline L.; Ruiz-Contreras, Alejandra E.; Prospéro-Garcia, Oscar
Highlights: Suppression of diacylglycerol lipase in the lateral hypothalamus prevented the increment in food intake induced by CHPG (mGluR1/5 agonist). Blockade of CB1 receptors (with AM251) in the lateral hypothalamus prevented the increment in food intake induced by CHPG (mGluR1/5 agonist). Lateral hypothalamic activation of mGluR1/5 increase food intake via endocannabinoid system. Abstract: Mounting evidence has shown that glutamatergic and endocannabinoid systems in the hypothalamus regulate mammalian food intake. Stimulation of hypothalamic mGluR1/5 and CB1 receptors induces hyperphagia suggesting a possible interaction between these systems to control food intake. In addition, synthesis of endocannabinoids has been reported after mGluR1/5 stimulation in the brain. The aim of this study was to examine the potential cannabinergic activity in the food intake induction by lateral hypothalamic stimulation of mGluR1/5. Wistar albino male rats received bilateral infusions in the lateral hypothalamus (LH) of: (i) vehicle; (ii) (RS)-2-Chloro-5-hidroxyphenylglycine (CHPG; mGluR1/5 agonist); (iii) 2-AG (CB1 endogenous agonist); (iv) AM251 (CB1 antagonist); (v) tetrahydrolipstatin (THL, 1.2 μg; diacyl-glycerol lipase inhibitor); and (vi) combinations of CHPG + with the other aforementioned drugs. Food intake was evaluated the first two hours after drug administration. CHPG significantly increased food intake; whereas CHPG in combination with a dose of 2-AG (with no effects on food intake) greatly increased food ingestion compared to CHPG alone. The increase induced by CHPG in food intake was prevented with AM251 or THL. These results suggest that activation of mGluR1/5 in the lateral hypothalamus induces an orexigenic effect via activation of the endocannabinoid system.